Cigarette Affordability in China, 2001-2016 - Zheng, Rong (World Bank, Washington, DC, 2017)
This study investigates the affordability of cigarettes in China between 2001 and 2016. In the past two decades, China has achieved unprecedented economic growth rates. The country’s per capita gross domestic product (GDP) has increased at an average annual rate of 10 percent. Rapid economic growth increases people’s purchasing power and makes cigarettes more affordable, as income gains overrun cigarette price increases. The results show that average-price cigarettes in China were 1.85 times more affordable in 2016 than in 2001, while the cheapest category of cigarettes, typically consumed by low-income persons, became 2.09 times more affordable over this period. Thus, cheap cigarettes aimed at low income Chinese consumers exhibit higher levels of affordability, and have increased their affordability faster, than other cigarettes aimed at average income consumers. The study estimates the affordability elasticity of cigarette consumption in China at -0.6, suggesting that a 10 percent increase in cigarette affordability will result in 6.01 percent increase in cigarette consumption. Cigarette affordability in China has also increased in comparison with other countries. China’s cigarette affordability was still at a low level compared with other countries in the 1990s, but increased quickly and to a high level within just two decades. Findings from this study have important implications for tax policy, pertaining to tobacco prices and tobacco control. These findings confirm that for tax increases to reduce the number of smokers and deaths in China, policy makers need to review the potential effects of rising income and prices with a focus on reducing cigarette affordability. It is also important to look at affordability not only on average but by income group - in this study proxied by using average and rural incomes.